Mahamanalactone A, a new triterpenoid from Dysoxylum malabaricum bark: a case study for rapid identification of new metabolites via LC-HRMS profiling and database mining strategy - Bhardwaj N.; Swathilakshmi S.; Tripathi N.; Kumar S.; Lal U.R.; G R.; Guru S.K.; Jain S.K. (My University, 2025)
In this recent investigation, the focus centred on exploring the potential phytoconstituents within the bark of Dysoxylum malabaricum. A profiling strategy employing LC-HRMS (Liquid Chromatography-High Resolution Mass Spectrometry) was implemented for the rapid identification of compounds from the bark extract. The crude extract underwent fractionation, resulting in the isolation of four previously known compounds (1–4) and a novel cycloartane triterpenoid named Mahamanalactone A (5). Compound 5 represents a cycloartane triterpenoid with a modified ring-A, featuring £-caprolactone fusion at positions 4 and 5, distinguishing it from other reported compounds where £-caprolactone is typically fused at positions 3 and 4. Cytotoxicity assessment revealed that the newly identified compound 5 exhibited a moderate cytotoxic profile (IC50 29 to 78 µM) against a panel of cancer cell lines. © 2024 Informa UK Limited, trading as Taylor & Francis Group.